2001
DOI: 10.1042/cs1020107
|View full text |Cite
|
Sign up to set email alerts
|

The response of liver albumin synthesis to infection in rats varies with the phase of the inflammatory process

Abstract: To discriminate between the effects of infection and of anorexia associated with infection, liver albumin synthesis was measured in well-fed rats, in rats injected with live Escherichia coli and in pair-fed rats at different stages of the inflammatory response (1, 6 and 10 days after infection) using a large dose of l-[1-(14)C]valine. Albuminaemia and albumin mRNA levels were unchanged following food restriction. However, absolute albumin synthesis was decreased in pair-fed rats compared with control animals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
41
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 26 publications
8
41
1
1
Order By: Relevance
“…Immunoadsorption (IA) was employed as an additional method for measuring the appearance rate of albumin and transferrin, modified from Ruot et al (31) with 3 H-labeled plasma from KO and WT mice at 90 min after administration of [ 3 H]leucine. Protein G-Sepharose (100 l; ϳ18 mg human IgG/ml drained beads; Amersham) was preequilibrated with Tris-buffered saline (TBS) and incubated with 100 l (1 mg/ml) of affinity-purified goat IgG against albumin or transferrin (Bethyl, Montgomery, TX) diluted in 200 l of TBS for 1 h at 4°C in an Ultrafree-MC centrifugal filter unit (Millipore, Billerica, MA) with gentle rocking.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoadsorption (IA) was employed as an additional method for measuring the appearance rate of albumin and transferrin, modified from Ruot et al (31) with 3 H-labeled plasma from KO and WT mice at 90 min after administration of [ 3 H]leucine. Protein G-Sepharose (100 l; ϳ18 mg human IgG/ml drained beads; Amersham) was preequilibrated with Tris-buffered saline (TBS) and incubated with 100 l (1 mg/ml) of affinity-purified goat IgG against albumin or transferrin (Bethyl, Montgomery, TX) diluted in 200 l of TBS for 1 h at 4°C in an Ultrafree-MC centrifugal filter unit (Millipore, Billerica, MA) with gentle rocking.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past half century, it has been reported that drug absorption and disposition can be altered during an inflammatory response because of modifications in plasma proteins, drug-metabolizing enzymes, and drug transporters (1). Downregulation of the levels of drug-binding plasma proteins and drug-metabolizing enzymes is now well identified, which translates into increased plasma drug concentrations or decreased clearance of drug substrates (2)(3)(4)(5)(6). More recently, inflammation-mediated regulation of drug transporters has been reported, especially for ATP-binding cassette (ABC) and solute carrier (SLC) transporters (1,5).…”
mentioning
confidence: 99%
“…In particular, a dynamic response (no change, a decrease, and then an increase) of albumin synthesis has been demonstrated in a rat model of sepsis [8]. Also, several studies in humans have shown a biphasic change of albumin synthesis in different phases of cholecystitis, which corresponds to studies in small animals.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, measurements of albumin synthesis in human beings have been conducted at only one time point, mostly during the acute phase, and several studies have addressed the possibility of albumin synthesis responding differently depending on the stage of the inflammatory process and various stimuli. In fact, a biphasic response (no change, then a decrease) of albumin synthesis has been confirmed in a rat model of sepsis [8]. The pathophysiologic process of intra-abdominal abscess following gastrointestinal fistula differs from those with an acute-phase response and possibly elicits different kinetics of albumin synthesis.…”
mentioning
confidence: 85%